Analysing the performance of small cardamom during pre and post WTO regime: Performance of small cardamom - Gopan, Arya; Mathews, Abin T (Journal of Spices and Aromatic Crops, 2025)
Indian agricultural trade has undergone significant changes during the last three decades, especially during the WTO regime. The small cardamom, which is regarded as the queen of spices, was one of the Indian spices that witnessed several setbacks during the WTO regime. In this context, the present study analyses the performance of variables like area, production, productivity, prices (domestic and international prices), exports, and imports of small cardamom in terms of growth rate, instability, and structural stability during the pre- and post-WTO periods. Unlike the area under small cardamom cultivation, the production and productivity of small cardamom increased during the post-WTO period. Consequent upon the new liberalised trade regime under the WTO, the CAGR of exports and imports has increased during the post-WTO. Prices of small cardamoms have been showing a decreasing trend since the 1980s. While the competitiveness of small cardamom declined, some of the major export destinations of Indian small cardamom remained the same, especially in the Middle East. Due to the unique quality of the Indian small cardamom, its demand has always been high in the international market, despite higher prices than in its competitors, like Guatemala. The higher cost of production, high domestic demand, and qualitative restrictions by importing countries have slackened the trade performance of Indian small cardamom, these can be overcome through promotion of sustainable farming practices and crop-specific plans and policies for enhancing crop production efficiency.